Nomes predicativos e construções neutras - Baptista, Jorge; Reis, Sónia; Mamede, Nuno (Revista da Associação Portuguesa de Linguística, 2022)
This paper, developed within the Lexicon‑Grammar theoretical and methodological framework, analyses the predicate noun and support‑verb constructions that admit the syntactic transformation: O médico fez um raio‑x ao tórax do Pedro = O Pedro fez um raio‑x ao tórax (lit.: ‘The doctor did a x‑ray to the chest of Pedro/Pedro did a x‑ray to the chest’) ‘The doctor x‑rayed Pedro’s chest/Pedro had a chest x‑ray’; in this sentence, raio‑x ‘x‑ray’ is a predicate noun and fazer ‘do’ is the support verb. The paper proposes to relate the two sentences by a formal operation, the Neuter transformation. About 275 predicate nouns, expressing a variety of semantic predicates, and involving body‑part nouns, admit this transformation. The paper aims to determine the lexical‑syntactic conditions to the application of the Neuter transformation, contrasting it with other transformations (Dative Restructuring, Conversion, and Fusion), and presents the main regularities observed, discussing the choice of a base form from the alternative sentences and its formalization within the lexicon‑grammar, a comprehensive data base of predicate nouns and support verb constructions currently with about 9,100 nominal predicates. The analysis is supported with data from corpora and other on‑line sources. The study is part of an on‑going program for the systematic description of the lexical‑syntactical properties of predicate noun constructions in European Portuguese.